Pendugaan Fungsi Keuntungan dan Skala Usaha pada Usahatani Kopi Rakyat di Lampung - Santoso, Budi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1987)
EnglishCoffee is a commodity classified as the one of the main contributors to the Government income through the small-scale coffee plantation farms. This paper tried to examine factors affected the rate of income earned from the farms, achievements of the profit maximization, and conditions resulted from the farm's return to scale. The research was conducted in Lampung during the harvest season in 1984/1985. The results show that the area of planted, the number of tress, and the age of the commodity were affected the profit earned from the farms with highly significant levels. The return to scale coefficient was calculated to be constant within the farm size average of 1.02 ha. Result was also indicate that the small-scale coffee farms in the location were hardly provide the maximum profit to the farmers.IndonesianKopi adalah salah satu komoditi penghasil devisa utama dari sub-sektor perkebunan yang sebagian besar (94%) diusahakan oleh rakyat. Tulisan ini mencoba menelaah faktor-faktor yang mempengaruhi tingkat keuntungan usahatani kopi rakyat, tercapai tidaknya keuntungan maksimum dan keadaan skala usaha. Penelitian ini dilaksanakan di Lampung untuk musim kopi 1984/1985. Hasil analisis menunjukkan bahwa luas kebun kopi, jumlah pohon kopi dan umur pohon kopi berpengaruh sangat nyata terhadap keuntungan usahatani kopi rakyat. Keadaan skala usaha adalah pada kondisi